THE APPLICATION OF VIDEO FEEDBACK TECHNOLOGY IN IMPROVING SHORT SERVE SKILLS IN BADMINTON - Faris, Faris Fawwaz; Oman Hadiana (Universitas Muhammadiyah Kuningan, 2025)
This study aims to determine the effect of applying Video Feedback (VFB) technology on improving short service skills in badminton games. The method used was an experiment with One Group Pretest-Posttest design on 10 students of Badminton UKM Muhammadiyah Kuningan University. Data were collected through short serve skill tests, observation, and video documentation. The results of the analysis showed a significant increase between pretest and posttest scores, with a significance value of 0.000 (p < 0.05), which indicated that VFB was effective in improving short service skills. These findings suggest that VFB can be an efficient and objective alternative learning method in sports training.